ANALISIS KOMPOSISI DAN KEANEKARAGAMAN VEGETASI TUMBUHAN BAWAH PADA TEGAKAN MAHONI (Swietenia mahagoni (L.) Jacq) DI KHDTK ULM KALIMANTAN SELATAN - Dwi Hargianto Nugroho; Basir Achmad; Setia Budi Peran (Jurnal Sylva Scienteae, 2023)
Covercrops communities in plantation forests are always synonymous with weeds which have long been seen as nuisance and harmful plants, especially in planted areas that are maintained. Covercrops plays an important role as a source of organic matter, reducing the kinetic energy of rain and the forces of runoff over the soil, to prevent erosion by water. The mahogany tree (Swietenia mahagoni (L.) Jacq) is one of the choices of species used in government programs in the green revolution movement. It is possible that in the future there will be lots of mahogany plants around us. This study aims to analyze the types of covercrops that exist in Mahogany (Swietenia mahagoni (L.) Jacq) including Relative Density, Relative Frequency, Important Value Index, analyze the dominance index of understorey species in the stand Mahogany (Swietenia mahagoni (L.) Jacq), and analyzed the diversity and evenness of covercrops species on Mahogany (Swietenia mahagoni (L.) Jacq) at KHDTK ULM which was the research location. The results of this study there are 16 species with a total of 384 types of undergrowth. The types obtained during data collection include alaban kapas, alang-alang, dambah, jawaling, juragi, karamunting, kopasanda, litu, madang pirawas, magatseh, mahang, pancing-pancing, papisangan, sarapangan, tampukas, tengkook ayam. The data from the calculation of understorey obtained the highest important value index of 49.48 from fishing rods, a dominance index of 0.13 which was included in the category of no dominant species, a diversity index of 2.26 which was included in the medium diversity category, and an evenness index of 0.38 which is included in the category of medium equity.Vegetasi yang menempati bagian bawah pada hutan tanaman terkadang identik dengan gulma yang sejak lama dipandang sebagai tanaman pengganggu dan merugikan terutama di areal tanaman yang dipelihara. Tumbuhan bawah berperan penting sebagai penyedia bahan organik, mengurangi kekuatan hempasan butiran air hujan dan kekuatan aliran pada permukaan tanah, untuk mencegah terjadinya erosi oleh aliran air. Pohon mahoni (Swietenia mahagoni (L.) Jacq) menjadi salah satu pilihan jenis yang digunakan pada program pemerintah dalam gerakan revolusi hijau. Hal ini pada masa depan tidak menutup kemungkinan akan ada banyak sekali tanaman dari jenis mahoni disekitar kita. Penelitian ini bertujuan untuk menganalisis jenis tumbuhan bawah yang ada pada Tegakan Mahoni (Swietenia mahagoni (L.) Jacq) meliputi Kerapatan Relatif, Frekuensi Relatif, Indeks Nilai Penting, menganalisis indeks dominansi jenis tumbuhan bawah pada tegakan Mahoni (Swietenia mahagoni (L.) Jacq), dan menganalisis keanekaragaman serta kemerataan jenis tumbuhan bawah pada Mahoni (Swietenia mahagoni (L.) Jacq) di KHDTK ULM yang menjadi lokasi penelitian. Hasil dari penelitian ini terdapat 16 jenis dengan total keseluruhan jumlah setiap jenis sebanyak 384 tumbuhan bawah. Jenis-jenis yang didapat selama pengambilan data diantaranya alaban kapas, alang-alang, dambah, jawaling, juragi, karamunting, kopasanda, litu, madang pirawas, magatseh, mahang, pancing-pancing, papisangan, sarapangan, tampukas, tengkook ayam. Data hasil perhitungan tumbuhan bawah diperoleh indeks nilai penting paling tinggi sebesar 49,48 dari jenis pancing-pancing, indeks dominansi sebesar 0,13 yang masuk dalam kategori tidak ada jenis yang mendominasi, indeks keanekaragaman sebesar 2,26 yang masuk dalam kategori keanekaragaman sedang, dan indeks kemerataan sebesar  0,38 yang masuk dalam kategori kemerataan sedang